BetaSys systems biology of regulated exocytosis in pancreatic ß-Cells - Booß-Bavnbek, Bernhelm; Klösgen, Beate; Larsen, Jesper; Pociot, Flemming; Renström, Erik (Springer eBooks., 2011)
Uses the example of regulated exocytosis in pancreatic β-cells, and its relevance to diabetes, to illustrate the major concepts of systems biology, its methods and applications. In using a focused approach here by picking one outlook, the topic of Systems Biology is made more accessible.Systems Biology is a fast moving field, but the work presented here emphasizes the principal aspects of the field, making this a tool for on-going research. The insulin secreting β-cell is one of the most specialized cell types with diverse and multi-functional components (genes, gene products, organelles and metabolites) and a multitude of regulatory strategies in response to internal and environmental signals. This book looks at the technological advances that make simultaneous detection of thousands of biological variables possible; at a substantial variety of mathematical models and numerical simulations that aim to explain major aspects of the β-cell function; and at the challenge to formulate a comprehensive and robust model of the main networks of the underlying biochemical and physical processes for diagnostic and therapeutic use